PENGELOLAAN PERPUSTAKAAN DIGITAL (Studi Situs di SMA Negeri 1 Semarang) - TAUFIK , IMAM (2011)
The objectives of this research are to describe (1) the digitalization characteristic of library collection, (2) the characteristic of library service, and (3) the characteristic of librarian activity in SMA N 1 Semarang. This research is qualitative research with ethnography design. This research is conducted in SMA N 1 Semarang. The human resources in this research are the chief of SMA N 1 Semarang library, librarian, teachers and students. The data collections used in this research are depth interview, observation, and documentation, while the data analyzed used site arrangement analysis. The result shows that (1) digitalization in reference such as book, magazine or newspaper through 3 steps that are scanning, editing, and uploading to the web. At first, the reference that will be scanned is chosen by librarian. Then, a librarian edited scanning text. The electronic document is saved in data base and will be uploaded to the internet. Physical reference is still needed. The use of digital library is still using books as physical reference. (2) Library service is given from 06.45 until 16.00 (for Monday-Thursday). Especially in Friday, the library starts from 06.45-11.30 and in Saturday starts from 06.45-13.30. Library service that's given is technical and reading service. Reading service is consisting of circulation service, reference service, reading service, internet service, photocopy service, video audio room service, and playing film service. Beside that, reading service is also can be done by online 24 hours with accessing the website www.smansalib.com. (3) The library starts from 06.45-15.30 a.m. in every Monday to Thursday. For Friday the library starts from 06.45-11.30 while in Saturday library starts from 06.45-13.30. The long schedule of library is aimed to give best service to the visitors. The librarian has long time job from Monday to Saturday. The librarian activities are divided into two activities, which are technical and reading service. Technical service does the activities of reference management such as arranging the data of books, inputting the data to main book, giving chop on book, classification, making catalogue, and entering data. Beside that, they also digitalizing the reference helped by freelance. Meanwhile, the activities of reading service are giving circulation service, reading service, reference service, photocopy service, playing film service, audio visual audio service, and internet service.